The rise of seniors as seniorpreneurs / Marlina Muhamad, Fariza Hanis Abd Razak and Haryani Haron - Muhamad, Marlina; Abd Razak, Fariza Hanis; Haron, Haryani (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Some researchers have conducted several studies on the m- learning. One study has looked into learning among university students in Malaysia. It is said that the university mobile services have given some positive impacts where the said services have been found to boost examination results and increase course registration Yaakub, 2011) (Naji Shukri Alzaza & Abdul Razak . It is important for the higher learning institutions to take of m-learning to move forward on the education aspect. note on the significance Older adult is believed to bring beneficial skills to the job, referred to as greater “crystallized intelligence”, which includes rhetorical ability and knowledge born of knowhow, as reported in a study in APA’s Journal of Applied Psychology (Harada et al., 2013). Crystallized intelligence is defined by Kensinger (2017) as the capacity to find and adapt the information that has been gained during a life period. It often is con tradicted with fluid intelligence, the capacity to keep and shape new information. Fluid intelligence mechanism tends to be agitated by healthy aging. Contradict to fluid intelligence, where crystallized intelligence, remains strong and balance across the life span. Thus, older adult are very excellent at interpreting words, response to questions that rely on general world knowledge, distinguish spelling inaccuracy, or carry out jobs that related to their skills they have held for many years (Kensinger, 201 7). Older adult can catch up for decreasing fluid intelligence by delineating on their crystallized intelligence. A result from studies analyzing productivity of young and old workers find that age is unreliable predictor of performance since crystallized intelligence increases with age with the accumulated knowledge by old people. Thus, engaged longer in workforce is an effective way to increase productive ageing (Belbase & Sanzenbacher, 2016). Research has found that older adult record higher levels of ‘c rystalized intelligence’ which wisdom gained through experience and verbal reasoning ability (Kensinger, 2017). For inspiration, a 93 year-- old Malaysia Prime Minister, Tun Mahathir, Malaysia’s oldest prime minister, who is back in charged in workforce today